Mapping indexes in rating estimation - Долгов, Олександр Іванович; Прокопенко, Олена Олександрівна (Technology audit and production reserves, 2014)
The comparability problem of numerical values (including quantitative-qualitative) of indexes in estimating a wide range of objects is solved in the paper. The method of parameters processing, in particular, reduction of their unbounded domain to the bounded, which is based on rationing is presented. The method of indexes mapping in rating estimation, which lies in dividing the value domain into several sections and boundary values mapping is given. New boundary values are rationed. The proposed method of indexes mapping in estimation allows to ensure results comparability in objects estimation. This allows to take into account the demands and wishes of people, who perform rating estimation, use its results and are interested in ensuring the correlation between the estimate obtaining rules and pragmatic goals.